2000
DOI: 10.1021/es001188p
|View full text |Cite
|
Sign up to set email alerts
|

Screening Potential of Solid-Phase Extraction Room Temperature Phosphorimetry for the Analysis of Polychlorinated Dibenzofurans in Water Samples

Abstract: Solid-phase extraction room-temperature phosphorimetry is evaluated for screening polychlorinated dibenzofurans in water samples. The organic pollutants are extracted from water samples on octadecyl bonded silica membranes. Water extraction is rapidly performed on a 13 mm disk by using a 100 mL syringe and a stainless steel filter holder. Room-temperature phosphorimetry is directly performed on the extraction membrane, which results in analysis times of approximately 10 min per sample. Limits of detection at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…After drying for 5 min, the tabs were examined via front surface room-temperature fluorescence spectroscopy to reach limits of detection (LODs) at the parts-per-billion (ng·mL − 1 ) level [5,13]. Later reports extended the use of SPE membranes to the room temperature phosphorimetry (RTP) analysis of PAHs [6,[14][15][16][17], polychlorinated biphenyls [15,17] and polychlorinated dibenzofurans [17]. Bulky glassware and vacuum pumps, common to classic SPE lab procedures, were replaced with a syringe kit well-suited for manual extraction under field conditions.…”
Section: Introductionmentioning
confidence: 99%
“…After drying for 5 min, the tabs were examined via front surface room-temperature fluorescence spectroscopy to reach limits of detection (LODs) at the parts-per-billion (ng·mL − 1 ) level [5,13]. Later reports extended the use of SPE membranes to the room temperature phosphorimetry (RTP) analysis of PAHs [6,[14][15][16][17], polychlorinated biphenyls [15,17] and polychlorinated dibenzofurans [17]. Bulky glassware and vacuum pumps, common to classic SPE lab procedures, were replaced with a syringe kit well-suited for manual extraction under field conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The present work represents a new development and application of analytical methods based on the selective adsorption of hydrophobic pollutants on a solid sorbent associated with spectroscopic detection directly applied on the solid substrate [19,20,21,22,23,24,25,26,27,28,29]. The evaluation of the potential of this approach for the analysis of 1-OHPy in human urine demonstrates that the method we propose is very sensitive and can be applied to the biological monitoring of people differently exposed or not to PAH.…”
Section: Discussionmentioning
confidence: 94%
“…Previous works [19,20,21,22,23,24,25,26,27,28,29] have shown that, using appropriate solid sorbent for extraction/concentration, it is possible to avoid the elution required in the solid phase and chromatographic steps by performing in situ spectroscopic detection of benzenic compounds [20], PAH [21,22,23,24,25,26,27] or polychlorobiphenyls [28,29] in aqueous solution directly on the solid phase. Recently, this approach has been proposed for the detection of 1-OHPy in human urine [24].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the biexponential decays obtained in the more complex systems are likely to result from their heterogeneous composition, which expose PABA molecules to different environments. 36 Interferences. With the aim of determining possible interferences with PABA phosphorescence by molecules bearing NH groups, compounds usually found in the same pharmaceuticals that contain PABA (with or without native phosphorescence) were investigated, namely nicotinamide, folic acid, pyridoxine (vitamin B 6 ), and cyanocobalamin (vitamin B 12 ).…”
Section: Solid Supportmentioning
confidence: 99%